Islamic Family Law and the Dynamics of Household Harmony: A Literature Review - Nahdiya ‘Atiqah (Lembaga Yasin AlSys, 2026)
Household harmony remains a central concern in contemporary Muslim family life, particularly amid social change, shifting family roles, and increasing marital conflict. This study examines the role of Islamic family law in achieving household harmony through a descriptive qualitative library research approach. Data were drawn from books, national and international journal articles, theses, laws and regulations, including Law No. 1 of 1974 and the Compilation of Islamic Law, and other relevant scholarly sources. The analysis synthesized conceptual and empirical literature on the purposes of marriage, spousal rights and obligations, child protection, conflict resolution, and the application of Islamic family law in contemporary society. The findings show that Islamic family law functions not only as a legal framework but also as an ethical and educational guide for fostering sakinah, mawaddah, and rahmah within the family. It supports household harmony by clarifying role distribution, promoting justice, protecting children’s rights, and institutionalizing deliberation (shura) and mediation (hakam) as mechanisms for resolving disputes and minimizing divorce. Effective implementation, reflected in mutual responsibility, open communication, equitable role-sharing, and child protection, is associated with stronger marital stability, improved child psychosocial well-being, and greater family resilience. Conversely, limited understanding or misapplication of Islamic family law principles may contribute to conflict, role uncertainty, and increased divorce risk. The study concludes that strengthening the comprehension and contextual application of Islamic family law is essential for sustaining harmonious and resilient Muslim households in the modern era. This study contributes to Islamic family law discourse by emphasizing its preventive, ethical, and restorative functions, with practical implications for premarital counselling, community education, and legal-social services.